Tennis elbow: survey among 839 tennis players with and without injury - Teixeira Silva, R.; Bannwart, M. (Medicine and Science in Tennis, 2008)
Background: Lateral epicondylitis, which is more commonly known as tennis elbow, is prevalent in the world of sports; however this injury still causes confusion among doctors and other healthcare professionals. Numerous studies have evaluated treatment options and prognosis, but few have taken into consideration the extent to which tennis players, themselves, understand this ailment. Objective: To determine to what level Brazilian tennis players understand the aetiology and courses of treatment for tennis elbow. Subjects: 839 tennis players who had been playing tennis for a mean age of 11 years. Methods: A simple, multi-choice questionnaire was made available on an internet site dedicated to tennis enthusiasts. Results: Among the players enrolled in this study, 41.8 % reported being affected by this injury. Despite the fact that nearly half of all tennis players had been affected, most players were unaware of the causes of tennis elbow. Even among those who had been affected by tennis elbow, only 39.3 % believed that the cause of the lesion was the backhand stroke, and almost all (94.9%) had undergone some form of treatment before seeking advice from a physician. Conclusions: We believe that this study demonstrates the need to properly educate players, coaches, and physicians so that they can better understand the clinical management of tennis elbow. Without such an understanding, tennis players tend to treat themselves and only seek medical advice during the chronic phase of the injury, when the prognosis is worse.